2001
DOI: 10.1083/jcb.153.5.999
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B Acts as a Dominant Execution Protease in Tumor Cell Apoptosis Induced by Tumor Necrosis Factor

Abstract: Death receptors can trigger cell demise dependent or independent of caspases. In WEHI-S fibrosarcoma cells, tumor necrosis factor (TNF) induced an increase in cytosolic cathepsin B activity followed by death with apoptotic features. Surprisingly, this process was enhanced by low, but effectively inhibiting, concentrations of pan-caspase inhibitors. Contrary to caspase inhibitors, a panel of pharmacological cathepsin B inhibitors, the endogenous cathepsin inhibitor cystatin A as well as antisense-mediated deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
587
3
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 583 publications
(621 citation statements)
references
References 46 publications
(66 reference statements)
26
587
3
5
Order By: Relevance
“…Expression of PS relies on activated caspase 3 in CD95-induced apoptotic cell death, whereas cathepsin B activity is necessary for PS expression in tumor necrosis factor-α-induced caspase-independent cell death 8,9 . Several studies have shown that pathways exist that cause cell surface expression of PS by living cells in specific conditions.…”
Section: Cell Death-independent Ps Externalizationmentioning
confidence: 99%
“…Expression of PS relies on activated caspase 3 in CD95-induced apoptotic cell death, whereas cathepsin B activity is necessary for PS expression in tumor necrosis factor-α-induced caspase-independent cell death 8,9 . Several studies have shown that pathways exist that cause cell surface expression of PS by living cells in specific conditions.…”
Section: Cell Death-independent Ps Externalizationmentioning
confidence: 99%
“…These modes of PCD are characterized by an essential activity of proteases other than caspases during the onset or execution phase of cell death. For example, cathepsins (Foghsgaard et al, 2001;Bidere et al, 2003;Broker et al, 2004), calpains (Karmakar et al, 2007;Pineiro et al, 2007) and yet uncharacterized proteases (de Bruin et al, 2003) were reported to play key roles in different cell death models.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In addition to the traditional apoptotic process mediated by caspases, other proteases such as the cathepsin cysteine proteases have been shown to participate in apoptotic signaling. [3][4][5][6][7][8][9][10][11][12][13][14] Although cathepsins normally reside in the lysosome and carry out nonselective degradation of proteins, a strong case was made for the involvement of these proteases in apoptosis when it was shown that agents that disrupted lysosomes and caused cathepsins to redistribute to the cytoplasm inevitably resulted in apoptosis. 13,[15][16][17][18][19] Similarly, cathepsin inhibitor treatment blocked this apoptosis.…”
Section: Introductionmentioning
confidence: 99%